Moderasi human capital pada pengaruh praktik manajemen sumber daya manusia terhadap inovasi layanan hotel di Yogyakarta - Hananto, Kombang (Journal of Management and Digital Business, 2024)
The tourism sector, supported by the hospitality industry, plays a vital role in a country's economy. This study mainly explores the relationship between Human Resource Management (HRM) and innovation in service and whether the relationship is mediated by human capital. Questionnaires were chosen to collect data from several four-star and five-star hotels in Yogyakarta. The proposed hypotheses were then tested by the Structural Equation Model (SEM) using smartPLS, for which questionnaires were used to collect data from 209 respondents in Yogyakarta hotels. The research findings prove that Human Resource Management positively influences hospitality Service Innovation in Yogyakarta and human capital activities. The results of this study will help the hospitality sector foster creativity in services through human resource management practices and build proper use of human capital in their employees through cultures of innovation. Modern human resources should know that internal customer (employee) satisfaction leads to external customer satisfaction.